Behavioral Artifacts: What is an Artifact? Or Who Does it? - Ken Friedman (Artifact, 2007)
Abstract The word “artifact” comes from two Latin words. The first, “arte”, means “by skill”, from “ars”, skill. The second, “factum”, is the past participle of “facere”, to do or to make.The word dates back to the early 1800s, meaning “something created by humans usually for a practical purpose; especially: an object remaining from a particular period” and “something characteristic of or resulting from a particular human institution, period, trend, or individual” (Merriam-Webster, 1990, p. 105). Most definitions focus on the quality of artifacts as things, speaking of objects and remains rather than process or production. Typical definitions are “anything made by human art and workmanship; an artificial product. In archeology, applied to the rude products of aboriginal workmanship as distinguished from natural remains”, “a product of human art or workmanship”, “any object made by human beings” (Oxford English Dictionary, 2006, n.p.; Shorter Oxford English Dictionary, 1993, p. 120; Wordsmyth, 2006, n.p.).I am as interested in the artifacts of doing as in the artifacts of making. Many artifacts exist only in human behavior, individual and social. These are the focus of this essay.